Evaluation of the awareness, expectations and satisfaction of patients undergoing orthognathic procedures - Szafran, Danuta; Miękus-Michalak, Katarzyna; Zawadzki, Paweł (Forum Ortodontyczne / Orthodontic Forum, 2020)
Skeletal and occlusal defects result in aesthetic and functional disorders. Being a combination of orthodontics and maxillofacial surgery, orthognathic treatment restores correct facial proportions and improves the functions of the stomatognathic system. Due to the duration of a treatment process and its complexity, the patient's conscious cooperation is crucial. Aim. The aim of the study was to examine the level of patients' awareness of various aspects of surgical treatment of gnathic defects, their expectations of these procedures, as well as their postoperative satisfaction with the treatment. Material and methods. The study group included 33 patients undergoing orthognathic procedures at the Department of Cranio-Maxillofacial Surgery, Oral Surgery and Implantology, the Medical University of Warsaw in the years 2013–2015. The survey consisted of three questionnaires: a questionnaire conducted before the procedure on the day of admission to the ward (T0) and postoperative questionnaires conducted on the day of suture removal, two weeks after the procedure (T1) and one year later (T2). The obtained results were subject to statistical analysis. Results. The level of being informed about the aim, course, outcomes of the procedure, as well as convalescence, was high (79 – 91%). Information about possible complications was not sufficient. Moreover, 78% of respondents were definitely and rather satisfied with the procedure one year after the procedure, and 93.8% reported that the outcomes corresponded to expectations. The main reason to undergo orthognathic treatment was to change facial features and to improve the alignment of teeth. Conclusions. Detailed information provided to patients about the course of a treatment process, including information about possible complications, seems to be extremely important for the outcomes of the procedure because it helps the convalescence process, increases patients’ compliance and acceptance of existing problems. The use of digital visualisation methods, treatment simulation, models and phantoms improves the effective communication between a patient and a doctor. (Szafran D, Miękus-Michalak K, Zawadzki P. Evaluation of the awareness, expectations and satisfaction of patients undergoing orthognathic procedures. Orthod Forum 2020; 16 (1): 5-26).